Legal Status and Institutional Position of Ma’had Darussalam Liltadrib Al-Islami Within the Framework of Religious Governance in Vietnam - Arifka Agus Diantara; Yulia Susantri (Fakultas Syariah INSURI Ponorogo, 2026)
This study aims to examine the legal status and institutional position of Ma’had Darussalam Liltadrib Al-Islami within the framework of regulations and religious governance in Vietnam. This institution is the only Islamic school in Tay Ninh Province that has obtained official government permission and plays a vital role in religious education for the Muslim minority community, particularly the Cham ethnic group. This research employs a normative juridical method using statutory and conceptual approaches, with John Rawls’ theory of justice as the analytical framework. The analysis focuses on the Law on Belief and Religion No. 02/2016/QH14, Decree No. 162/2017/ND-CP, and the Education Law No. 43/2019/QH14. The findings indicate that Ma’had Darussalam Liltadrib Al-Islami holds legal status as a state-recognized non-governmental religious educational institution after fulfilling administrative requirements. However, it is not integrated into the government's institutional structure, as Vietnam's political system places religion within the socio-cultural sphere rather than within the state's political or administrative structure. This study offers new contributions by explaining the dynamics between legal recognition and state supervision of religious educational institutions in a socialist state, while enriching comparative studies on religious governance in Southeast Asia.